Simplify :4a - [3a - b -{2a - 3b -(2a + 5 - a)}]
Answers
Answered by
2
Answer:
4a-[3a-b-{2a-3b-(2a+5-a)}]
=4a-[3a-b-{2a-3b-(a+5)}]
=4a-[3a-b-{2a-3b-a-5}]
=4a-[3a-b-{a-3b-5}]
=4a-[3a-b-a+3b+5]
=4a-[2a+2b+5]
=4a-2a-2b-5
=2a-2b-5
Answered by
1
Answer:
2(a-b) -5
Step-by-step explanation:
4a-[3a-b-{2a-3b-(2a+5-a)}]
4a-[3a-b-{2a-3b-a-5}]
4a-[3a-b-{a-3b-5}]
4a-[3a-b-a+3b+5]
4a-[2a+2b+5]
4a-2a-2b-5
2a-2b-5
2(a-b)-5
Similar questions
World Languages,
2 months ago
Hindi,
2 months ago
History,
2 months ago
Math,
5 months ago
English,
5 months ago
Math,
1 year ago
Computer Science,
1 year ago